Niger - Impacts of Sustainable Land Management Programs on Land Management and Poverty in Niger - World Bank (World Bank, 2012)
Since the early 1980s, the Government of Niger and its development partners have invested more than 200 billion West African Francs (FCFA) in programs will promote sustainable land management (SLM) and other activities to reduce poverty and vulnerability. Overall, more than 50 programs have promoted SLM in Niger. Despite large investments in SLM programs, their impacts on land management, agricultural production, poverty, and other outcomes are not well known. A few studies have documented impacts of particular projects and land management practices in selected locations, finding many favorable impacts. However, although these studies provide valuable insights, they are limited in scope and by the methods used. A common problem is the absence of suitable counterfactual observations to compare to outcomes for communities and households participating in programs or using particular land management practices, or inadequate definition of the counterfactual used. This analysis is intended to contribute to knowledge about the impacts of SLM programs in Niger by addressing some of the methodological limitations of prior studies. The evaluation is based on a secondary database of major SLM program activities and village characteristics assembled for all villages of Niger, and a community and household survey conducted with more than 1,200 households in 139 villages selected to represent the rural regions of Niger where most SLM programs have operated. Threats to external and internal validity of the findings were addressed by using statistical sampling methods to assure representativeness of the findings, and quasi-experimental matching and econometric methods to assure that the program and counterfactual non-program villages and households were as comparable as possible in terms of observable characteristics that affect program placement, participation, and outcomes.